Conservation genetics of Sclerocactus in Colorado: the importance of accurate taxonomy to conservation - McGlaughlin, Mitchell E.; Naibauer, Samantha K. (Frontiers in Conservation Science, 2023)
Recent advances in genetic data collection utilizing next-generation DNA sequencing technologies have the potential to greatly aid the taxonomic assessment of species of conservation concern, particularly species that have been difficult to describe using morphology alone. Accurate taxonomic descriptions aided by genetic data are essential to directing limited conservation resources to species most in need. Sclerocactus glaucus is a plant endemic to Western Colorado that is currently listed as Threatened under the Endangered Species Act (ESA). However, in 2023, the U. S. Fish and Wildlife proposed de-listing S. glaucus from the ESA due to recovery of the species. Previous research had found substantial genetic structure between populations in the northern part of the S. glaucus range relative to the majority of the species distribution. In this study we utilized double-digest Restriction-site Associated DNA sequencing (RAD-seq) in order to better understand the genetic structure of S. glaucus. Our results indicate that S. glaucus contains two distinct evolutionary lineages that warrant recognition at the level of species, with what was previously described as S. glaucus North being recognized as Sclerocactus dawsoniae McGlaughlin and Naibauer (McGlaughlin and Naibauer in press). The newly described S. dawsoniae has a limited estimated number of individuals, low levels of nucleotide diversity, a very narrow geographic range,and an uneven geographic distribution with most plants being found in a single management area, all of which supports continued direct conservation of this species. In contrast, S. glaucus has a large estimated minimum population size, a broad geographic range that includes numerous protected This is a provisional file, not the final typeset article areas, and adequate levels of genetic diversity. Without further conservation action, a delisting decision for S. glaucus will simultaneously remove all Endangered Species Act protections for S. dawsoniae. The current work demonstrates the importance of having robust genetic datasets when planning conservation activities for species of concern. Moving forward, we recommend that government stakeholders prioritize supporting genetic studies of endangered species prior to making any changes to listing decisions.